Nilai Pendidikan Karakter dalam Folklor Ratu Kalinyamat Jepara - Noor Fatmawati; Achmad Faizal Dito Farezi (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2023)
This study aims to describe folklore of Ratu Kalinyamat and the value of character education in the folklore of Ratu Kalinyamat in Jepara. This study uses a descriptive qualitative method with a phenomenological approach. The object of this research is the folklore of Ratu Kalinyamat which has been passed down from generation to generation. There are 3 important informants who are the sources of data from this research, namely: the caretaker of the Astana Mosque, Sultan Attends, Pilgrims of the Queen Kalinyamat Tomb, and the Mantingan village community. Data obtained through in-depth interviews, observation and documentation. The data analysis technique used is an interactive model data analysis technique which consists of four stages, namely (1) data collection; (2) data reduction; (3) data analysis (4) drawing conclusions. The value of character education in the folklore of Ratu Kalinyamat is in the form of religious values; Tolerance; hard work, creative, and independent; as well as the spirit of nationality and love for the Motherland. These values are a form of transfer of values from Ratu Kalinyamat to the village community and the next generation in general.